Talking by numbers: Communicated uncertainty of the ECB - Oliver Sauter; Sebastian Schroff; Ulli Spankowski; Hans-Peter Burghof (Intereconomics, 2013)
Using a novel approach, this paper analyses the deliberately communicated uncertainty of the ECB to the market. Specifically, it semantically analyses the uncertainty expressed in official ECB press statements. The analysis shows how the ECB tries to alert or appease the market with different levels of communicated uncertainty. The appeasement through low uncertainty communication levels is particularly pronounced during times of financial distress. Further, the analysis shows that the ECB tried to alert the market through an increasing level of communicated uncertainty prior to the outbreak of the global financial crisis.
Keywords: 330; Geldpolitik; Staatliche Information; Zentralbank; EU-Staaten